Quantitative and functional alterations of 6-sulfo LacNac dendritic cells in multiple myeloma. (3rd July 2018) - Lamarthée, Baptiste; de Vassoigne, Frédéric; Malard, Florent; Stocker, Nicolas; Boussen, Inès; Médiavilla, Clémence; Tang, Ruoping; Fava, Fanny; Garderet, Laurent; Marjanovic, Zora; Brissot, Eolia; Mohty, Mohamad; et al.
ABSTRACT: Multiple myeloma (MM) results from expansion of abnormal plasma cells in the bone marrow (BM). Previous studies have shown that monocytes play a crucial role in MM pathophysiology. A 6-sulfo LacNAc-expressing population of dendritic cells (Slan-DCs) that overlaps with intermediate and non-classical monocytes in terms of phenotype has been described. Slan-DCs represent a circulating and tissue proinflammatory myeloid population which has been shown to play a role in different cancer contexts, and which exhibits a remarkable plasticity. Herein, we studied Slan-DCs from the BM and blood of MM patients. We performed quantitative and functional analyses of these cells from 54 patients with newly diagnosed, symptomatic MM, 21 patients with MGUS and 24 responding MM patients. We found that circulating Slan-DCs were significantly decreased in MM patients as compared to those of healthy donors or patients with MGUS, while CD14+CD16+ intermediate monocytes accumulate in the BM. Moreover, after activation with TLR7/8 ligand R848, IL-12-producing Slan-DCs from the BM or peripheral blood from MM patients were decreased as compared with healthy donors. We show that MM cell lines or MM cells isolated from patients at diagnosis were able to inhibit the production of IL-12 by Slan-DCs, as well as to shift the phenotype of Slan-DCs towards an intermediate monocyte-like phenotype. Finally, Slan-DCs that have been cultured with MM cells reduced their capacity to induce T cell proliferation and Th1 polarization. We conclude that Slan-DCs represent previously unrecognized players in MM development and may represent a therapeutic target.